Modelling Infectiology of Bursal Disease in Chicks with Control Measures - Hugo, Alfred; E. Kitengeso, Raymond; Lusekelo, Eva (Global Journal of Mathematical Analysis, 2021)
This paper focuses on mathematical control of infectious bursal disease in chicks. The model boundedness and the control measures to reduce the spreads of the disease have well analytically examined. The theory of Pontryagin’s maximum principle used in analysing necessary conditions to combat the disease. Numerically, forward backward sweep method and fourth-order Runge-Kutta scheme using the forward solution of the state equations was applied. The outcome indicates that the combination of vaccination of chicks and environmental sanitation as the most cost-effectiveness strategy to combat the spread of IBD with limited resources. Therefore, IBD can be controlled if the poultry farmers will effectively apply vaccination of chicks and environmental sanitation.